Demographic and socioeconomic determinants of influenza vaccination disparities among university students. Issue 9 (14th October 2009) - Uddin, M; Cherkowski, G C; Liu, G; Zhang, J; Monto, A S; Aiello, A E
Abstract : Background: The Advisory Committee on Immunization Practices encourages dormitory residents to receive influenza vaccination. To our knowledge, there are no studies that have directly examined factors associated with vaccination uptake among university students residing in dormitories. We therefore sought to examine the influence of demographic, social and health behaviours on influenza vaccination coverage among college dormitory students. Methods: Cross-sectional analysis of baseline questionnaire data obtained from 845 eligible participants in a non-pharmaceutical intervention study for reducing influenza during the 2007–2008 influenza season. Significant predictors were identified through logistic regression analysis with generalised estimating equations to account for resident clustering. Results: Increasing parental educational attainment was significantly associated with a trend in higher vaccination uptake among students: college graduate versus some college or less (OR 3.48, 95% CI 1.33 to 9.12) and some postgraduate education versus some college or less (OR 5.89, 95% CI 2.35 to 14.80) (trend test p<0.001). Adjusting for covariates, reported influenza vaccination for the 2007–2008 influenza season was strongly associated with reported influenza vaccination for the 2006–2007 influenza season (OR 16.38, 95% CI 9.28 to 28.91) and with speaking to a health professional about precautions to take against influenza (OR 2.95, 95% CI 1.42 to 6.13). Conclusions: The effect of parental educational status on vaccination rates can carry over to offspring, even among those who attain college student status. Programs targeting students who are employed on campus and who have never been vaccinated may be an especially effective way to increase vaccination rates, as both of these factors were significantly related to parental socioeconomic status in this study.